ANALYZING CRITICAL THINKING IN ENGLISH READING MATERIALS USING CAMBRIDGE LIFE COMPETENCIES FRAMEWORK - mardhiyatu zakiyah; Sri Sumarni; Darmahusni Darmahusni (ELTIN Journal, 2023)
The research intended to analyze English reading materials in terms of critical thinking skills aspect utilizing Cambridge Life Competencies Framework for critical thinking. This research employed a content analysis study in two coursebooks. The method used to gather the data were content analysis, library research, and need analysis. While, to analyze textual data and find the most appropriate data set, the researchers employed a color-coding technique for themes and ideas. This finding revealed that two English reading textbooks accommodated 8 of the 11 components of critical thinking skills according to the Cambridge Life Competencies Framework. The eight components fall into two main parts: comprehension and analysis of concepts and arguments and evaluation of ideas and claims. However, the three components of critical thinking skills which are in one core area, namely: solving problems and making decisions have not been accommodated in all English reading materials. Thus, the study recommends that the development of English reading materials in relation to critical thinking skills that refer to Cambridge Life Competencies framework needs to be carried out so that learners are capable of thinking clearly and logically about what they desire and what they feel is the best course of action for learning reading.   Keywords: Cambridge Life Competencies Framework, Critical Thinking Skills, English Reading Materials, Seventh Graders.